Effect of Anti-Infective Reconstituted Bone Xenograft Combined with External Fixator on Serum CRP and PCT Levels and Prognosis of Patients with Bone Infection after Lower Extremity Long Bone Trauma. (31st August 2021) - Wang, Fei; Liu, Yang; Qiu, Xiaofeng; Fei, Hao; Liu, Wei; Yuan, Kun
Abstract : Bone infection is one of the common complications of orthopedic surgery. After bone trauma occurs in the human body, the infection of Staphylococcus aureus and Gram-negative bacteria into the fracture area can lead to double infection of the soft tissue and bone tissue at the fracture site, leading to a variety of complications, mostly in the lower extremities. Bone infection easily causes bone destruction, bone nonunion, and bone defect, seriously affecting the quality of life of patients. The traditional treatment method of bone infection is to control the infection first and then repair the bone graft, but this method has a long course, poor efficacy, and high disability rate. In this study, anti-infective reconstituted bone xenograft (ARBX) combined with external fixation was used to treat patients with posttraumatic bone infections of the long bones of the lower extremities, to explore its efficacy, and to analyze its effects on serum CRP, PCT levels, and prognosis. Our results showed that ARBX combined with the external fixator had a good effect on the treatment of patients with bone infection after lower extremity long bone trauma, which could effectively enhance the repair and functional recovery of the limb bone, significantly alleviate the infection degree of patients, reduce the inflammatory response of the body, and have a good prognosis.